ANALISIS PERMINTAAN TENAGA KERJA DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - B21110016, Muhammad Parwis (Jurnal Pembangunan dan Pemerataan, 2017)
Employment issues are very complex issues which the growth of the labor force that is not accompanied by job creation will result in resources and labor potential becomes unbalanced. This study aims to examine and analyze the influence of Investment, Gross Domestic Product (GDP) and the Minimum Wage Labor demand in the District / City of West Kalimantan Province. This study uses panel data (cross section and time series) through multiple linear regression method with fixed effect model approach and the use of tools Eviews 0.7 program. Observation of the data as much as 70 in 14 districts / cities in West Kalimantan in 2010 through 2014These results indicate that the investments have a significant effect on the demand for labor in the District / City of West Kalimantan Province, Gross Domestic Product (GDP) significantly affects the demand for labor in the District / City of West Kalimantan Province and the minimum wage has no significant effect on the Demand for labor in the District / City of West Kalimantan Province. Â  Keywords: Labor Demand, Investment, the GDP and the Minimum Wage